Metal functionalization of two-dimensional nanomaterials for electrochemical carbon dioxide reduction. Issue 14 (23rd March 2023) - Wang, Guozhi; Ma, Yangbo; Wang, Juan; Lu, Pengyi; Wang, Yunhao; Fan, Zhanxi
Abstract : Electrochemical carbon dioxide reduction offers a promising strategy to achieve carbon neutrality. Here we review the latest important advances of metal-functionalized 2D nanomaterials for electrocatalytic carbon dioxide reduction reaction (CO2 RR). Abstract : With the mechanical exfoliation of graphene in 2004, researchers around the world have devoted significant efforts to the study of two-dimensional (2D) nanomaterials. Nowadays, 2D nanomaterials are being developed into a large family with varieties of structures and derivatives. Due to their fascinating electronic, chemical, and physical properties, 2D nanomaterials are becoming an important type of catalyst for the electrochemical carbon dioxide reduction reaction (CO2 RR). Here, we review the recent progress in electrochemical CO2 RR using 2D nanomaterial-based catalysts. First, we briefly describe the reaction mechanism of electrochemical CO2 reduction to single-carbon (C1 ) and multi-carbon (C2+ ) products. Then, we discuss the strategies and principles for applying metal materials to functionalize 2D nanomaterials, such as graphene-based materials, metal–organic frameworks (MOFs), and transition metal dichalcogenides (TMDs), as well as applications of resultant materials in the electrocatalytic CO2 RR. Finally, we summarize the present research advances and highlight the current challenges and future opportunities of using metal-functionalized 2D nanomaterials in the electrochemical CO2 RR.